Alfa glucosidase inhibitory, anti inflammatory activities and a new furanocoumarin derivative of Ruellia tuberosa. Issue 22 (18th November 2021) - Trinh, Pham Thi Nhat; Giang, Bach Long; Tuan, Nguyen Trong; Hang, Hoang Thi Thu; Thuy, Nguyen Thi Le; Tuan, Nguyen Ngoc; Dung, Le Tien
Abstract: Rullia tuberosa L. is used for treatment of diabetes mellitus, anti-inflammation, etc. However, its hypoglycaemic and anti inflammatory activities has not been investigated so far. In the present study, the α-glucosidase inhibitory, anti inflammatory activities of the extract of this plant were investigated. Our results showed that the crude extract as well as ethyl acetate and methanol fractions showed α-glucosidase inhibitory activity with IC50 of 15.84, 4.73 and 8.27 µg/ml, respectively. In addition, the hexane and ethyl acetate fractions are capable of inhibiting LPS-induced NO production with IC50 of 17.41 and 23.95 µg/mL, respectively. From the ethyl acetate and methanol fractions, eight compounds, including isobargaptol 5-O-β-D-glucopyranoside (1 ), syringaresinol (2 ), catechin (3 ), pulmatin (4 ), stigmast-4-en-3-on (4 ), verbascoside (5 ), hydroxymethylfurfural (6 ), rutin (7 ), and homoplantaginin (8 ) were extracted and isolated. Their chemical structures were elucidated by spectroscopic method including MS, 1 D and 2 D- NMR and comparison with the literature values. Graphical Abstract: